2008
DOI: 10.1093/jac/dkn106
|View full text |Cite
|
Sign up to set email alerts
|

Increased resistance to cationic antimicrobial peptide LL-37 in methicillin-resistant strains of Staphylococcus aureus

Abstract: Clinical strains of MRSA, but not MSSA, that demonstrated an increased net charge also showed elevated resistance to LL-37, but not to hBD3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 10 publications
2
54
0
Order By: Relevance
“…MRSA possesses a large repertoire of established ROS and AMP resistance mechanisms (49,60,61), and this may provide functional redundancy that allows greater compensation for loss of bNOS expression. The regulatory effects of endogenous NO are also likely to differ among species, just as differential adaptive responses of S. aureus and B. anthracis to exogenous NO have been described (22,62).…”
Section: Discussionmentioning
confidence: 99%
“…MRSA possesses a large repertoire of established ROS and AMP resistance mechanisms (49,60,61), and this may provide functional redundancy that allows greater compensation for loss of bNOS expression. The regulatory effects of endogenous NO are also likely to differ among species, just as differential adaptive responses of S. aureus and B. anthracis to exogenous NO have been described (22,62).…”
Section: Discussionmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) of MelitAP-27, antibiotics, and the peptide-antibiotic combinations against the bacterial strains mentioned previously was determined by adapting the microbroth dilution method outlined by the Clinical and Laboratory Standards Institute (CLSI) guidelines (Komatsuzawa et al 2000;Ouhara et al 2008). Briefly, bacterial cells were grown over night in Muller Hinton Broth and diluted to 10 6 CFU/ml in the same medium prior to use.…”
Section: Bacterial Susceptibility Assaymentioning
confidence: 99%
“…Previous studies had indicated potent activity of LL-37 against most strains of S. aureus (27,28), with MICs in the lower micromolar range and comparable only to the MICs for E. coli. However, a recent study of clinical isolates of S. aureus has found a broad range of susceptibilities to LL-37 in both MSSA and MRSA strains (21). One of the factors contributing to the resistance of some strains of S. aureus to LL-37 is the presence of proteolytic enzymes (25).…”
Section: Micsmentioning
confidence: 99%